2011
DOI: 10.1111/j.1365-2095.2009.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of fish meal with raw or treated cowpea (Vigna unguiculata L Walp, IT86-D719) meal in diets for Nile tilapia (Oreochromis niloticus L.) fry

Abstract: Two feeding experiments were carried out to evaluate the effect of partial substitution of fish meal (FM) with raw or heat‐treated cowpea Vigna unguiculata L. Walp var. IT86‐D719 seeds on growth performance, digestibility and pancreas tissue in Nile tilapia (Oreochromis niloticus L.) fry. Experiment 1 involved six isonitrogenous and isocaloric diets: four containing different concentrations of raw, whole cowpea meal (protein basis), a positive control with FM as sole protein source and a negative with cowpea m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
2
10
0
3
Order By: Relevance
“…The latter study reported ADP of 79.4% and 88.0% for toasted and cooked beans, whereas in the present investigation using dehulled bean meal resulted in ADP as high as 89.3% and 92.0%. A study shown to be similar to our results reported ADP of 90–91% in diets for tilapia using dehulled Vigna unguiculata …”
Section: Discussionsupporting
confidence: 92%
“…The latter study reported ADP of 79.4% and 88.0% for toasted and cooked beans, whereas in the present investigation using dehulled bean meal resulted in ADP as high as 89.3% and 92.0%. A study shown to be similar to our results reported ADP of 90–91% in diets for tilapia using dehulled Vigna unguiculata …”
Section: Discussionsupporting
confidence: 92%
“…At the global level, alternative protein sources for fish culture have been studied intensively during the last few decades because of the declining availability and high cost of fish meal [3][4][5]. A large number of plant products have been evaluated as potential protein sources in the diets for fish including cottonseed meal, sunflower meal and corn meal [6], soybean meal, cassava leaf meal, sweet potato leaf meal, groundnut cake [7], pea, horsebean and rapeseed plant protein concentrates [8], Jatropha kernel meal [9], cowpea [10] and lupin meal [11]. Despite the abundance of a large number agro-industrial by-product in Ghana, their potential as cheap ingredients for fish feed formulation remains to be fully exploited.…”
Section: Journal Of Animal Research and Nutrition Issn 2572-5459mentioning
confidence: 99%
“…Ainda assim, é seguro afi rmar que os farelos processados tenham ampliado seu potencial de uso. Contudo, a efi ciência de utilização dos farelos tratados dependerá da sensibilidade da espécie de peixe enfocada a diferentes tipos e teores de antinutrientes (OLIVERA-CASTILLO et al, 2011), tendo infl uência direta nos níveis de inclusão desses ingredientes em dietas para peixes. Muitas vezes, em determinadas regiões, há carência de indústrias produtoras de diferentes concentrados proteicos.…”
Section: Resultsunclassified
“…Esses estudos estão contribuindo para a geração de informações tanto a respeito da fi siologia da digestão e exigências nutricionais das principais espécies, quanto sobre o processamento de outros ingredientes a serem utilizados em dietas para aquicultura (MWACHIREYA et al, 1999;FUH & CHIANG, 2001;GATLIN III et al, 2007;PICKARDT et al, 2009;OLIVERA-CASTILLO et al, 2011).…”
Section: Introductionunclassified